(untitled) (Proceedings of Southern Federal University. Philology, 2023)
DOI 10.18522/1995-0640-2023-1-33-45 Abstract. Chekhov’s drama “Three Sisters” is the richest of all Chekhov’s plays in terms of sound design – despite a number of scientific works devoted to the sound score of the play, it still attracts the attention of researchers in this aspect. Today it seems relevant to consider the sounds, noises, musical fragments of the drama, recorded by the author in the remarks and text, constituting an integral part with the semantic field of the drama. This article shows that the sound concept of the play was carefully thought out by Chekhov in relation to the images he created and the events unfolding in the play – for each act and the play as a whole, and therefore the sound palette of the drama is its integral part and should be read by the directors as part of the author’s intention. Examples of sound design of several significant performances in the history of the world theater of different years staged by K.S. Stanislavsky, Vl.I. Nemirovich-Danchenko, A.V. supplementing the article, actualize attention to the sound palette of the play and expand the possibilities of interpreting the Chekhov’s play. Key words: Chekhov, Three Sisters, remarks, noises, music, sound score of the play, interpretation